Flower morphology, floral development and insect visitors to flowers of Nepenthes mirabilis (Biodiversitas Journal of Biological Diversity, 2017)
Handayani T. 2017. Flower morphology, floral development and insect visitors to flowers of Nepenthes mirabilis. Biodiversitas 18: 1624-1631. Nepenthes mirabilis Druce is a commercial ornamental pitcher plant belonging to the Nepenthaceae. This species is often used as a parent plant in artificial crossbreeding. The plant is also used in traditional medicine, rope-making, handicraft, and bouquets. Flower development and pollen maturity are important factors in pitcher plant crossbreeding. However, information about its flowering is still lacking. This study aimed to record the flower morphology, flower development, and faunal visitors to male inflorescences of N. mirabilis planted in Bogor Botanic Gardens, West Java, Indonesia. Twelve racemes of flowers were taken as a sample for observing the process of inflorescence development, while ten flowers on each raceme were observed for investigating the flowering pattern of individual flowers. The morphology of flowers, the process of inflorescence development, the flowering pattern for individual flowers, the number of open flowers, the longevity of anthesis, and the appearance of insect (and/or other faunal) visitors to flowers were observed and recorded, using naked eyes, a hand lens, and a camera. Six phases of inflorescence development were identified: inflorescence bud phase, raceme phase, the opening of the raceme-protecting sheath phase, inflorescence-stalk and flowerstalk growth phase, open flower phase and pollen maturity phase. Four phases of flower development were observed: growth of flower bud, the opening of tepals, pollen maturation, and flower senescence. The pattern of anthesis within an inflorescence was acropetal. The number of flowers per raceme was 56 to 163. The peak duration of anthesis of a flower was 11 days (30.7% of flowers). The length of the raceme-stalks was 17-31 cm. The length of the racemes was 23-38 cm. The most common visitors to the flowers were stingless bees, Trigona apicalis.
Keywords: Flower; Nepenthes mirabilis; pitcher plant; pollen; raceme